PELAKSANAAN SISTEM PENGUPAHAN BURUH PABRIK BATU BATA DI KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Wages are workers 'or workers' rights that are received and expressed in the form of money in return from employers or employers for workers or laborers who are determined and paid according to a work agreement, agreement, or legislation including benefits for workers or laborers and their families for an work or service that has been or will be performed. Wages are often equated with the salary of a worker or labor force. In the implementation of the provision of wages or wages the system has been regulated in Law Number 13 of 2003 concerning Labor. But in reality the remuneration system is still not in accordance with the written agreement and is only based on verbal so that there is no concrete work agreement, one of which is in the Batubata Factory in Pekanbaru City. An unwritten wage system is still in place, a payment system with daily wages and no employment contract in an employment agreement. The problems and objectives that will be discussed in this thesis are to find out how the implementation of the Batubata Factory wage labor system in Pekanbaru City Based on Law Number 13 Year 2003 Regarding Employment.This type of research is a survey, which is conducting a survey to the field at the site and at the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted at Batubata factory workers in Pekanbaru city and to the employment department and Batubata factory workers. while the population and sample are the whole of the parties related to the problem under study in this study the source of the data used are primary secondary data and Tertiary data data collection techniques in this study with questionnaire interviews and literature studies.The results of this study can be concluded that the implementation of the brick factory workers wage system in the city sub-district in the city of Pekanbaru based on law number 13 of 2003 concerning employment has not been running well and is not yet optimal, this is because the system implemented by the Batubata business owner is still experiencing the crisis in the payment of wages to factory workers and the method of payment is to use the system per day and not in accordance with the needs needed by the factory workers.Keywords: Implementation - Wage system - Batubata factory workers - Employment